2023
DOI: 10.3389/fpsyg.2023.1131076
|View full text |Cite
|
Sign up to set email alerts
|

Risk perception of COVID-19 and its related factors among centralized medical isolation groups in China

Abstract: ObjectiveMedical isolation is one of the most effective measures to slow the spread of the virus when dealing with a pandemic. Millions of people in China have undergone centralized medical isolation (CMI) during the COVID-19 pandemic. This study aims to assess the centralized medical isolation group’s COVID-19 risk perception and to explore the influencing factors.MethodsA total of 400 participants (200 who had experienced CMI and 200 who had not experienced) completed a questionnaire related to COVID-19 risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
1
1
Order By: Relevance
“…26 COVID-19 risk perception and behavior can be influenced by a higher level of education among populations. 37 While some studies have not observed any associations between educational level and COVID-19 vaccine uptake, 38 our findings contradict those found in Ethiopia where vaccine uptake was lower among participants who had a higher level of education and had attended college or university possibly due to their increased access to information and awareness of the potential side effects and safety. 26,39 Risk perception is a critical factor in vaccine decisions.…”
Section: Vaccine Uptake Over Timecontrasting
confidence: 80%
“…26 COVID-19 risk perception and behavior can be influenced by a higher level of education among populations. 37 While some studies have not observed any associations between educational level and COVID-19 vaccine uptake, 38 our findings contradict those found in Ethiopia where vaccine uptake was lower among participants who had a higher level of education and had attended college or university possibly due to their increased access to information and awareness of the potential side effects and safety. 26,39 Risk perception is a critical factor in vaccine decisions.…”
Section: Vaccine Uptake Over Timecontrasting
confidence: 80%
“…Household composition, more specifically the presence of children in the household, can also affect perception of risk during the pandemic. The existing literature has found that people living in families with children had higher risk perception as they were concerned about their children getting infected with COVID-19; as a result, they were willing to put in more effort to reduce their exposure to the virus [ 85 ].…”
Section: Consumer Adoption Of Online Grocery Shopping: Theoretical Mo...mentioning
confidence: 99%